The importance of road infrastructure as the backbone of transport system - Lum, Yuk Ping; Melan, Mustakim (2012)
The research focuses on the importance role of road infrastructure in the transport system for the country and the reason of inefficient road infrastructure.The research aims to discuss the role of government to improve the road infrastructure by the few method technology such as technology in order to enhance the construction road infrastructure.The research methodology uses the secondary data to analysis the importance of road infrastructure.As a conclusion, the effects road infrastructures are based on the construction project management and infrastructure management.